Pengaruh Kadar Albumin Serum terhadap Penyembuhan Luka pada Pasien Pascaoperasi Laparotomi dan Lumbotomi di RSD dr. Soebandi Jember - Meytika Fauziah Sugiartanti; Duriyanto Oesman; Ulfa Elfiah (Pustaka Kesehatan, 2018)
Wound healing need protein as basis for the formation of collagen network. The important component of protein is albumin. The aim of this study was to investigate albumin serum’s effect on wound healing in patients postoperative laparotomy and lumbotomy at dr. Soebandi Hospital Jember. The method of study was analytic observational with cross sectional design. Total samples in this study were 9 samples. The results showed that the higher albumis, the faster wound healing. Data analysis using bivariate analyzing Spearman's Rho test showed that the significance (p)=0.011 and correlation coefficients (r)=0.791. Thus, it can be concluded that there were a strong albumin serum’s effect of wound healing in patients postoperative laparotomy and lumbotomy at RSD dr. Soebandi Jember.